Appraisal of ablution station at mosque for people with disabilities : learning from the past, designing for the future / Nur Aqilah Azahar and Md Azree Othuman Mydin - Azahar, Nur Aqilah; Mydin, Md Azree Othuman (2018)
A mosque is not only something that will normally use by Muslims but it will be visited by various kind of person including handicapped people. Therefore, a mosque must be universally designed to cater all kinds of users, including People with Disabilities (PWDs), the elderly and not to forget children. In this case, facilities is a must thing that should be considered while designing the mosque especially ablution. For followers of Islam, ablution is a state that is prerequisite for praying. This research is aiming to identify the present of design of feasible and user-friendly ablution station at the Mosques in state of Penang for People with Disabilities (PWDs). There are two methodologies will be used in this research to collect all related data. The first one is Access Audit. This method will be used in order to know the current condition and facilities that are being provided in the ablution station at the mosque. The next is semi-structured interview which in purpose to collect all the data related to the mosque from persons or committee that responsible for it. Results from the case studies had shown that there are many important element that need to be provided in the ablution area for PWDs especially seats, water taps, finishing materials such as accessories like handrails, signs for PWDs as well as barrier provisions.